ANALISIS PENGENDALIAN KUALITAS REFINED BLEACHED DEODORIZED PALM KERNEL OLEIN MENGGUNAKAN METODE QUALITY LOSS FUNCTION DI PT. XYZ - Rifka Amalia; Margie Subahagia Ningsih; Rizkha Rida (Bajang Institute, 2026)
PT. XYZ is a company engaged in the palm oil processing industry, producing various products derived from palm oil, with Crude Palm Kernel Oil (CPKO) as the raw material. One of the products resulting from the CPKO processing is Refined Bleached and Deodorized Palm Kernel Olein (RBDPKL). The products produced have a range of quality characteristics and quality standard specifications that have been established. However, in practice, the quality of the Refined Bleached Deodorized Palm Kernel Olein (RBDPKL) produced by PT. XYZ at certain times still does not meet the company’s standard specifications. The Quality Loss Function method is one of the quality control methods used to determine the impact of product variation on production costs. This method provides a functional relationship between product deviations and losses. From the analysis and processing of data on two parameters, color and FFA, it was found that the raw material factor is the main cause of product defects. This is due to the presence of raw materials that do not meet the established standards. The company’s loss on the RBDPKL product, calculated using the